A MODIFIED METHOD OF SPECTRAL ANALYSIS OF RADIO SIGNALS USING THE OPERATOR APPROACH FOR THE FOURIER TRANSFORM - Sobchuk, Valentyn; Laptiev, Serhii; Laptievа, Tetiana; Barabash, Oleg; Drobyk, Oleksandr; Sobchuk, Andrii (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
The article proposes the improved method of spectral analysis of radio signals. The improvement is achieved due to the use of special operators in the signal conversion process. This allows you to distinguish the signal accurately and to determine its characteristics at the background of many airspace obstacles. The obtained graphical results fully confirm the advantages of the proposed method. The simulation results proved the advantage of the improved method of spectral analysis of radio signals; the advantage is achieved through the usage summing matrix functions in the process of signals conversion. The proposed improved method increases the accuracy of signals detection of secretly obtaining information means by 12%.